Development of an Indirect ELISA for the Detection of Lactoferrin in Type 2 Diabetes Plasma: A Novel Approach - Alhalwani, Amani (Current Analytical Chemistry, 2024)
Background: In biological systems, lactoferrin (LF) is a crucial protein for protecting the body against diseases and pathogens that can affect both humans and animals. LF is a multifunction protein that binds to different surface receptors to stimulate the innate immune system. In diabetes, lactoferrin has a direct association with inflammation. The effects of inflammation interaction are unknown but reasonably could include changes in LF, a body protein whose changed concentration correlates with type 2 diabetes (T2D). The LF content in plasma has been used as a disease biomarker, and there is a need for convenient and reliable assays. Method: An innovative indirect enzyme-linked immunosorbent assay (ELISA) was developed and applied to measure circulating lactoferrin levels as an inflammation marker in human samples, including healthy and type 2 diabetes. Results: Under optimized conditions, the proposed indirect ELISA was evaluated and linearly responded to LF standards in a 0.05–0.5 μgmL−1 range. The limit of detection (LOD) was 0.05 μgmL−1, and a reliable limit of quantification (LOQ) was 0.240 μgmL−1. Conclusion: The developed assay showed both specificity and reproducibility, indicating the utility of this indirect ELISA in LF monitoring. This study provides a definitive indirect ELISA protocol to detect various lactoferrin antigens with accurate, reliable, and reproducible data, and it could be applied for diagnosing lactoferrin-related diseases, such as type 2 diabetes. Our innovative approach provides a relatively cost-effective, sensitive, and precise way to assess LF in various human plasmas.
Keywords: lactoferrin (LF)